102Assessing the characteristics of health state utilities among people living with multiple sclerosis. (2nd September 2021) - Campbell, Julie; Jelinek, George; Weiland, Tracey; Nag, Nupur; Neate, Sandra; Palmer, Andrew; Mulhern, Brendan; Livera, Alysha De; Simpson-Yap, Steve
Abstract: Background: While many studies have examined the impacts of multiple sclerosis (MS) on health-related quality-of-life (HRQoL), none have used the SF-6D multi-attribute utility instrument in a large international cohort (>2, 000 subjects) of people with MS. Our objective was to derive SF-6D health state utilities (HSUs) for participants of the HOLISM international cohort and to describe the distribution and determinants thereof. Methods: HSUs were generated using the SF-6D for the Version-1 United States SF-36 for participants with sufficient SF-36 data (n = 2, 185/2, 466 (88.6%)). Determinants of HSU were evaluated by linear regression, adjusted for age, sex, MS type, disability (Patient-Determined MS Severity Scale), fatigue (Fatigue Severity Scale), and prescription antidepressant use. Results: Mean HSU for the sample was 0.67 (SD = 0.13) and diminished with increasing MS-related disability. These findings were robust to adjustment, supporting the SF-6D's discriminatory power in people with MS. Severe disability and clinically significant fatigue were each associated with 11%-lower HSU (95%CI=-0.13, -0.10 & -0.12, -0.10), and depression risk (Patient Health Questionnaire-2) with 10%-lower HSU (95%CI=-0.11, -0.08). Employment, higher socioeconomic and married/partnered statuses, larger social-network size, greater physical activity, vitamin D and omega-3 supplementations were associated with significantly higher HSU, and overweight/obese BMI and tobacco smoking with lower HSU. Age, sex, and education were not associated. Conclusions: The SF-6D revealed significant discriminatory power for the HOLISM international cohort. Modifiable lifestyle factors including diet, physical activity and supplement use for the international cohort were robustly associated with increased HSU and thus HRQoL. Confirmatory longitudinal HSU evidence could provide further support to our baseline findings using the SF-6D. Key messages: Health state utilities in this sample of people living with MS were moderate and were significantly lower among those with greater disability, fatigue, and depression, while some lifestyle factors like physical activity and supplement use were associated with higher utility scores.